2018
DOI: 10.1590/0037-8682-0400-2017
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibodies in Chinese patients with tuberculosis

Abstract: ANCA positivity may be more related to vasculitis and immunological disorders than to a M. tuberculosis infection. Therefore, to improve diagnostic accuracy, patients with M. tuberculosis who are ANCA positive should be investigated for concurrent diseases, including the effects of drugs. Therefore, even in tuberculosis epidemic area, ANCA seropositivity, detected by ELISA, is still more suggestive of ANCA-associated vasculitides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The fact that the second ANCA test came back positive led to early closure of our clinical reasoning. The association between positive ANCA serology and infections such as tuberculosis and MAC has been described previously [9,10]. However, it is not clear whether the presence of ANCA truly reflects a vasculitis induced by mycobacteria or merely a clinical non-significant antibody induced by the infection.…”
Section: Discussionmentioning
confidence: 95%
“…The fact that the second ANCA test came back positive led to early closure of our clinical reasoning. The association between positive ANCA serology and infections such as tuberculosis and MAC has been described previously [9,10]. However, it is not clear whether the presence of ANCA truly reflects a vasculitis induced by mycobacteria or merely a clinical non-significant antibody induced by the infection.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, Gao Huan et al determined the presence of ANCAs in patients with TB. Even though the measure of ANCAs was not performed in our research, it would be worth investigating an association among ANCAs positive vasculitis, TB diagnosis, and the expression of the TNF-α soluble receptors in further studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 50 AAV case reports, three species of bacteria (Streptococci, Staphylococci, and Enterococci) were associated with 63% of the reported episodes of infectious endocarditis and 42% of all infections reported. 25 Huan et al 26 recently demonstrated that ANCA-positivity in patients with Mycobacterium tuberculosis infection is related to AAV, so the detection of ANCA in these patients must be excluded because GPA and MPA can present with clinical features that overlap with those of tuberculosis. Among the viruses suspected to play a pathogenic role in AAV, parvovirus B19, 27 Epstein-Barr virus, 28 and Ross River virus have been reported.…”
Section: Environmental Associations and Immunogenicity Of Anti-neutro...mentioning
confidence: 99%